Optimizing the Power of Action Learning : Real-Time Strategies for Developing Leaders, Building Teams and Transforming Organizations /: Real-Time Strategies for Developing Leaders, Building Teams and Transforming Organizations. (2018) - Marquardt, Michael J; Banks, Shannon; Cauwelier, Peter; Ng, Choon Seng
No abstract available